Social Feeding Behavior of Trichoplax adhaerens - Fortunato, Angelo; Aktipis, Athena (Frontiers in Ecology and Evolution, 2019)
Animals have evolved different foraging strategies in which some animals forage independently and others forage in groups. The evolution of social feeding does not necessarily require cooperation; social feeding can be a beneficial individual-level strategy if it provides mutualistic benefits, for example though increasing the efficiency of resource extraction or processing. We found that Trichoplax adhaerens, the simplest multicellular animal ever described, engages in social feeding behavior. T. adhaerens lacks muscle tissue, nervous and digestive systems – yet is capable of aggregating and forming groups of closely connected individuals who collectively feed. The tight physical interactions between the animals are transitory and appear to serve the goal of staying connected to neighbors during the external digestion of algae when enzymes are released on the biofilm and nutrients are absorbed through the ventral epithelium. We found that T. adhaerens are more likely to engage in social feeding when the concentrations of algae are high - both in a semi-natural conditions and in vitro. It is surprising that T. adhaerens – an organism without a nervous system – is able to engage in this social feeding behavior. Whether this behavior is cooperative is still an open question. Nevertheless, the social feeding behavior of T. adhaerens, an early multicellular animal, suggests that sociality may have played an important role in the early evolution of animals. It also suggests that T. adhaerens could be used as a simple model organism for exploring questions regarding ecology and sociobiology.